Keratinocytic Malfunction as a Trigger for the Development of Solar Lentigines - Marjam Jeanette Barysch; Ralph Peter Braun; Isabel Kolm; Verena Ahlgrimm-Siesz; Rainer Hofmann-Wellenhof; Christine Duval; Emilie Warrick; Francoise Bernerd; Stéphanie Nouveau; Reinhard Dummer (MDPI AG, 2019)
Introduction: Solar lentigines (SL) affect chronically UV-radiated skin. Treatment is often refractory. Deeper knowledge on its pathogenesis might improve therapeutic effects. Material and Methods: Morphological characterization of 190 SL was performed and epidermal thickness, pigment distribution, dendricity, and cornification grade were measured. Immunoreactivity was investigated using Melan A, Tyrosinase, MITF, p53, and CD20, as well as Notch1 using immunofluorescence. Results: We found 2 groups of histological patterns, i.e., either acanthotic or atrophic epidermis. Lesions with basket-woven cornification and atrophic epidermis were observed in 6 out of 9 and 14 out of 16 cases from the face, respectively. Consistency of areas with a high pigmentation was observed in 96-97% of the cases. Hyperpigmentation grade and acanthosis or cornification disorders correlated positively in 88.5% of the cases. Overexpressed of p53 was found in 19 out of 20 lesions, presenting in a scattered distribution. A significant correlation of p53 and acanthosis (p = 0.003) and cornification grade (p = 0.0008) was observed. Notch1 was expressed in all SL, with the highest immunoreactivity in atrophic facial lesions. Lesions from the hands expressed Notch1 mainly in acanthotic areas with elongated rete ridges and less compact cornification. Discussion: We suggest that Notch1-dependent keratinocytic malfunction causes the development of SL. Consequently, hyperpigmentation would be a result and not the primary cause of the pathogenesis. Confirmation of these findings might have clinical implications as hitherto treatment has mainly focused on melanocytes and pigmentation and not on the proliferation/differentiation balance of keratinocytes.